ANALISIS TENTANG KEPUASAN PELANGGAN MENGGUNAKAN METODE LEAN STARTUP PADA MENU MASAKAN “WARUNG MAK ASEP” - Prasiska Adela Susilowati; Sri Rahayu; Tata Sutabri (Jurnal Salome : Multidisipliner Keilmuan, 2024)
Warung Mak Asep is a Startup that is engaged in the production of healthy food in the form of vegetable boxes, fruit juices and sharing information about health. This study aims to develop a business model for Startup Warung Mak Asep Lean Canvas with the Lean Startup. The method in the data analysis process is using qualitative methods. Primary data was obtained from conducting a semi-structured interview process with a total of 10 informants. At this stage of research, the stages of the Lean Startup are Build, Measure and Learn to develop and innovate Warung Mak Asep products. At the Build stage, which is the stage of making a Minimum Viable Product (MVP), Measure is the validation stage by collecting validation data using the Empathy Map tool, the Javeline Board with the results that 8 out of 10 people state the product is valid and at the Learn, which is the result of benchmarks for innovation. towards products and innovate business models with the Lean Canvas tool. Lean Canvas is a business model adaptation of the Business Model Canvas used because it is valid for implementation on a startup. The Lean Startup can reduce the failure and costs that will be incurred by Startup for product development in accordance with the input and wishes of the customer.